Over-Expression of MicroRNA-210 and MicroRNA-185-5p in Normotensive Late-Fetal Growth Restriction: Preliminary Cohort Study - Altan Erbilen, Esra; Varol, Gulizar Fusun; Sut, Necdet; Turker, Nebiye Pelin; Sayin, Niyazi Cenk (Gynecology Obstetrics & Reproductive Medicine, 2024)
OBJECTIVE: Late Fetal Growth Restriction (LFGR), a condition associated with perinatal and long-term neurodevelopmental problems, is caused by inadequate placental transfer of oxygen and nutrients to the fetus. This preliminary study evaluates the expression profiles and clinical significance of hypoxia-sensitive microRNA-210 (miR-210) and microRNA-185-5p (miR-185-5p) in placental and maternal circulation. The potential clinical implications of this research could significantly enhance the management of LFGR. STUDY DESIGN: In this prospective cohort study conducted at the Gynecology and Obstetrics Clinic of Trakya University Faculty of Medicine Hospital, miR-210 and miR-185-5p expression was evaluated in the placenta of healthy (n=30) and LFGR (n=30) cases. In healthy (n=15) and LFGR (n=15) cases, miRNA levels in maternal plasma were studied. We determined these two miRNAs using Real-Time Quantitative Polymerase Chain Reaction (RT-qPCR) and statistically analyzed them with clinical data to determine robustness. We provided a comprehensive evaluation. RESULTS: Both the placenta and maternal plasma samples exhibited significant correlations with miR-210 and miR-185-5p expression (r=0.615; r=0.771, p<0.01). The expression levels in both placenta and plasma were significantly higher in the LFGR group. Placental miR-210 demonstrated an AUC (0.908), sensitivity (93.3%), and specificity (96.7%), while plasma miR-210 showed AUC (0.738), sensitivity (86.7%), and specificity (66.7%). In contrast, placental miRNA 185-5p displayed a diagnostic performance with AUC (0.926), sensitivity (76.1%), and specificity (63.8%); plasma miRNA 185-5p exhibited an AUC (0.778), sensitivity (86.7%), and specificity (86.7%). However, placental miR-210 and miR-185-5p did not fully correlate with birth weight, placental weight, and fetal cerebroplacental Doppler ratio. CONCLUSION: Placental miRNA-210 showed superior diagnostic performance over placental miRNA 185-5p in LFGR pregnancies. However, it is crucial to emphasize that further studies are needed to validate these findings and correlate them with clinical data, underscoring the ongoing importance of research in this field.